(untitled) (Dhaka University Journal of Science, 2020)
The present study focuses on the utilization of non-edible Aphanamixis polystachya seed oil as a potential feedstock for the production of biodiesel. The extracted oil from non-edible seed could not be directly exploited for biodiesel production owing to its high free fatty acid (FFA) content of 5.785%, so acid catalyzed esterification was applied to reduce FFA of oil to zero followed by base-catalyzed transesterification to convert esterified product to its mono-esters. Thermogravimetric analysis (TGA) revealed that the mass percentage corresponding to biodiesel under optimum conditions was 74.38%. The conversion of the triglycerides in the oil into biodiesel through transesterification was confirmed using FT-IR spectroscopy. The elemental analysis of the produced biodiesel was studied. The produced biodiesel had properties which were comparable with biodiesel standards and could be utilized as an alternative diesel fuel without any hardware modifications. Dhaka Univ. J. Sci. 68(2): 129-136, 2020 (July)